Update on Dementia - Vito Moretti, Davide (IntechOpen, 2016)
The dementia challenge is the largest health effort of the times we live in. The whole society has to move to a realization of the significance of prioritization to make an attempt in the direction of mental health promotion and dementia risk reduction. New priorities for research are needed to go far beyond the usual goal of constructing a disease course-modifying medication. Moreover, a full empowerment and engagement of men and women living with dementia and their caregivers, overcoming stigma and discrimination should be promoted. The common efforts and the final aim will have to be the progress of a ''dementia-constructive'' world, where people with dementia can take advantage of equal opportunities.